One Health investigation and response to a nationwide outbreak of Rift Valley fever in Rwanda – March to December 2022 - Leandre Ishema; Soledad Colombe; Fabrice Ndayisenga; Evodie Uwibambe; Eline Van Damme; Marie Meudec; Edson Rwagasore; Denyse Mugwaneza; Wim Van Bortel; Anselme Shyaka (One Health)
Rift Valley fever (RVF) is an emerging zoonotic mosquito-borne disease caused by Rift Valley Fever virus (RVFV), affecting both humans and animals. It is endemic to Rwanda and Tanzania and Uganda which are adjacent countries, with possible transboundary transmissions. Despite the various outbreak reports in Rwanda since 2012, information on the intensity and spread of these outbreaks and their management is scarce. We describe the 2022 outbreak that happened in Rwanda and provide insights into the One Health response implemented during the outbreak.There were no human cases officially reported. A total of 1339 confirmed RVF animal cases were identified from 21 March until 31 December 2022. The breakdown of the cases per livestock species showed 1285 (96%) cases in cattle, 34 (3%) in goats and 20 (1%) in sheep. Of the confirmed livestock cases, 516 died and 1254 abortions were registered, in all affected species.The outbreak response was characterized by extensive interventions such as animal spraying with pyrethroid insecticides, vaccinations, and active follow-up of animals and humans in the households with animal cases. In the first phase of the outbreak, animal movements and slaughtering were restricted in the highly affected regions. Gradually, the abattoir slaughter activities were resumed with all animals required to test negative by RT-PCR before slaughter. Remarkably, the public services and hospital laboratories supported both capacity building of veterinary laboratory scientists and testing of animals' samples. The overall response was coordinated by district cross-sectoral teams linking national and community-level actors. Outbreak-related information was synthesized by the district teams and shared at national level while national strategies were communicated to the affected communities through the district structures.Rwanda's response to RVF provides a proof of concept that multisectoral efforts involving community members in a One Health approach can offer efficient response to zoonotic outbreaks while still protecting the country's economy.